Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Spin-orbit driven electrical manipulation of the zero-field splitting in high-spin centers in solids - Biktagirov, Timur; Gerstmann, Uwe (Physical Review Research)
Keywords: General Engineering

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

A photoredox catalysed Heck reaction via hole transfer from a Ru(ii)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg; Gerstmann, Uwe; Meier, Armin; Schmidt, Wolf Gero; Wilhelm, René (RSC Advances)
A hole transfer from an excited Ru unit towards graphene oxide significantly improved the photocatalytic activity of the complexes.
Keywords: General Chemical Engineering; General Chemistry

Vibration-Driven Self-Doping of Dangling-Bond Wires on Si(553)-Au Surfaces - Braun, Christian; Neufeld, Sergej; Gerstmann, Uwe; Sanna, S.; Plaickner, J.; Speiser, E.; Esser, N.; Schmidt, Wolf Gero (Physical Review Letters)

Investigation of Near-Surface Defects of Nanodiamonds by High-Frequency EPR and DFT Calculation - Cho, F. H.; Peng, Z.; Biktagirov, T.; Gerstmann, Uwe; Takahashi, S. (The Journal of Chemical Physics)

Proton Irradiation Induced Defects in β-Ga2O3: A Combined EPR and Theory Study - von Bardeleben, Hans Jürgen; Zhou, Shengqiang; Gerstmann, Uwe; Skachkov, Dmitry; Lambrecht, Walter R. L.; Ho, Quoc Duy; Deák, Peter (APL Materials)

Excited-state band mapping and momentum-resolved ultrafast population dynamics in In/Si(111) nanowires investigated with XUV-based time- and angle-resolved photoemission spectroscopy - Nicholson, C. W.; Puppin, M.; Lücke, A.; Gerstmann, Uwe; Krenz, Marvin; Schmidt, Wolf Gero; Rettig, L.; Ernstorfer, R.; Wolf, M. (Physical Review B)

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Electron Paramagnetic Resonance Tagged High-Resolution Excitation Spectroscopy of NV-Centers in 4H-SiC - Zargaleh, S. A.; von Bardeleben, H. J.; Cantin, J. L.; Gerstmann, Uwe; Hameau, S.; Ebl\'e, B.; Gao, Weibo (Phys. Rev. B)

Unraveling the Oxidation and Spin State of Mn–Corrole through X-ray Spectroscopy and Quantum Chemical Analysis - Paszkiewicz, Mateusz; Biktagirov, Timur; Aldahhak, Hazem; Allegretti, Francesco; Rauls, Eva; Schöfberger, Wolfgang; Schmidt, Wolf Gero; Barth, Johannes V.; Gerstmann, Uwe; Klappenberger, Florian (The Journal of Physical Chemistry Letters)

Identifying On-Surface Site-Selective Chemical Conversions by Theory-Aided NEXAFS Spectroscopy: The Case of Free-Base Corroles on Ag(111) - Aldahhak, Hazem; Paszkiewicz, M.; Rauls, E.; Allegretti, F.; Tebi, S.; Papageorgiou, A. C.; Zhang, Y.-Q.; Zhang, L.; Lin, T.; Paintner, T.; Koch, R.; Schmidt, Wolf Gero; et al. (Chemistry - A European Journal)

Impact of finite-temperature and condensed-phase effects on theoretical X-ray absorption spectra of transition metal complexes - Müller, Patrick; Karhan, Kristof; Krack, Matthias; Gerstmann, Uwe; Schmidt, Wolf Gero; Bauer, Matthias; Kühne, Thomas D. (Journal of Computational Chemistry)

Polytypism driven zero-field splitting of silicon vacancies in 6H-SiC - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe; Yavkin, Boris; Orlinskii, Sergei; Baranov, Pavel; Dyakonov, Vladimir; Soltamov, Victor (Physical Review B)

Spin pairing versus spin chains at Si(553)-Au surfaces - Braun, Christian; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)

Calculation of spin-spin zero-field splitting within periodic boundary conditions: Towards all-electron accuracy - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

X-Ray Magnetic and Natural Circular Dichroism from First Principles: Calculation of K- and L1-Edge Spectra - Bouldi, N.; Vollmers, N. J.; Delpy-Laplanche, C. G.; Joly, Y.; Juhin, A.; Sainctavit, Ph.; Brouder, Ch.; Calandra, M.; Paulatto, L.; Mauri, F.; Gerstmann, Uwe (Physical Review B)

X-ray Spectroscopy of Thin Film Free-Base Corroles: A Combined Theoretical and Experimental Characterization - Aldahhak, Hazem; Paszkiewicz, M.; Allegretti, F.; Duncan, D. A.; Tebi, S.; Deimel, P. S.; Casado Aguilar, P.; Zhang, Y.-Q.; Papageorgiou, A. C.; Koch, R.; Barth, J. V.; Schmidt, Wolf Gero; et al. (The Journal of Physical Chemistry C)